The Influence of Service Promotion and Work Productivity on Customer Decision to Saving at PT Bank Muamalat Indonesia KCP Bantul - Ratih (JOURNAL OF ISLAMIC ECONOMICS AND BUSSINES ETHICS, 2024)
The purpose of this study was to determine the effect of promotion, service, and productivity as well as the simultaneous and partial influence on the customer's decision to save at PT. Bank Muamalat Indonesia KCP Bantul. Research method through observation, questionnaires, and documentation. The library materials are then analyzed with written source guidelines and concluded. From the results of this study, the authors found that the results of this study indicated that 76.3% of the dependent variable in saving decisions could explained by the independent variables namely promotion, service, and work productivity. While the remaining 23.7% was caused by other variables not involved in this study such as product image, service quality, customer value, etc. The t-test on the promotion, service, and work productivity variables shows that the count obtained exceeds the table so it can be said that the promotion, service, and work productivity variables have a positive and significant effect on saving decisions. The partial test shows that the regression coefficients for the promotion, service and work productivity variables exceed the significant value so that together the promotion, service, and work productivity variables have a positive/significant effect on saving decisions.